Intersecting identities of elite female boxers: Stories of cultural difference and marginalization in sport - Blodgett, A. T.; Ge, Y.; Schinke, R. J.; McGannon, K. R. (Psychology of Sport and Exercise, 2017)
Objectives: The project responds to calls for research that attends to issues of cultural diversity within sport and that facilitates expanded understandings of socially constructed identities. The intersecting identities of elite female boxers are explored in terms of how they shape experiences of marginalization and well-being within sport. Focus is on constructions of race and ethnicity, language, and religion. Design: An intersectional lens grounded in social constructionism was integrated with a cultural sport psychology approach to espouse the complexity, fluidity, and multi-dimensionality of the athletes` identities as the product of intersecting narratives. Methods: Mandala drawings and conversational interviews were employed as open-ended data collection processes that enabled the participants to share their identities. Portrait vignettes were then developed as creative nonfiction to elucidate how identities dynamically intersect and shape sport experiences. Results: Five portrait vignettes layer together to show issues of identity expression, oppression and White privilege within the boxing context. The stories provide contextual insight into the ways in which athletes continually construct and negotiate identities in relation to dynamics of difference and sameness. They move fluidly between identities that are valued and identities that are marginalized, moments of open expression and moments of concealment. Conclusions: The research contributes to social justice missions within sport by illuminating how certain identities result in individuals being dis/advantaged, socially excluded, and discriminated against. Possibilities are revealed for challenging social inequalities and facilitating more inclusive sport spaces that resonate with who athletes are as holistic, multifaceted people.